(untitled) (CIPEEX, 2022)
FAKE NEWS, WHICH DOMINATED THE WORLD STAGE IN THE US PRESIDENTIAL ELECTIONS IN 2016, HAS BECOME AN INCREASINGLY PRESENT AND UNCOMFORTABLE REALITY NOT ONLY IN BRAZIL, BUT THROUGHOUT THE WORLD. WITH THE POPULARIZATION OF THE INTERNET AND SOCIAL NETWORKS, THE SHARING OF FABRICATED, FALSE OR INACCURATE NEWS HAS GROWN EXPONENTIALLY. THE ’FAKES NEWS’ SHARED ON THE INTERNET ARE PART OF A PROBLEMATIC PANORAMA OF DISINFORMATION AND, ACCORDING TO SODR (2019, P.99), €ŒTHEY ARE OF THE NATURE OF RUMOR, TO BE RECEIVED LESS FOR THEIR FACTUAL CONTENT AND MORE FOR THEIR FABULATION NARRATIVE, IN THE WAY OF A DELIBERATE PERVERSE FAIT-DIVERS€. FILHO (2019), ON THE OTHER HAND, DRAWS ATTENTION TO THE OFFENSIVE USE OF COMPUTERS, KNOWN AS €ŒROBOTS€, WHICH COPIOUSLY REPRODUCE, IN A VIRAL AND IMMEASURABLE WAY, THE SAME FAKE NEWS IN COUNTLESS POSTS WITH THE AIM OF OPPRESSING DIVERGENT OPINIONS, ESPECIALLY DURING ELECTORAL PERIODS.